2022
DOI: 10.1007/s00586-022-07509-z
|View full text |Cite
|
Sign up to set email alerts
|

Are respiratory disorders risk factors for troublesome neck/shoulder pain? A study of a general population cohort in Sweden

Abstract: Purpose The etiology of neck/shoulder pain is complex. Our purpose was to investigate if respiratory disorders are risk factors for troublesome neck/shoulder pain in people with no or occasional neck/shoulder pain. Methods This prospective cohort study was based on the Stockholm Public Health Cohorts (SPHC) 2006/2010 and the SPHC 2010/2014. We included adults who at baseline reported no or occasional neck/shoulder pain in the last six months, from the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…As demonstrated in multiple studies in different countries, the prevalence of LBP is clearly higher in women (60% vs. 40%) [28]. Migraine, which affects 12.6% of the general population, is more than twice as prevalent in women (17.2% vs. 8%) [29], and NP affects more women in all age groups [12].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…As demonstrated in multiple studies in different countries, the prevalence of LBP is clearly higher in women (60% vs. 40%) [28]. Migraine, which affects 12.6% of the general population, is more than twice as prevalent in women (17.2% vs. 8%) [29], and NP affects more women in all age groups [12].…”
Section: Discussionmentioning
confidence: 89%
“…Neck pain (NP) is one of the most common musculoskeletal disorders, with an estimated prevalence of around 10-20% in adults [7]. Few studies have evaluated the association between asthma and NP [10][11][12][13][14]. A recent study suggests that patients with asthma have a higher risk of NP over time [12], and it offers several explanations for this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In chronic respiratory disease and during induced hypercapnia, postural activation of these muscles is impaired. 10 A recent systematic review found that there is not much research on non-drug treatments for post-viral syndromes and COVID-19. The reviewers found randomized clinical trials that were done in 2021 that looked at music therapy, telerehabilitation, resistance therapy, and neuromodulation, but they did not look at all the symptoms experienced in these cases, focusing only on dyspnea, arthralgia, general pain, and quality of life.…”
Section: Introductionmentioning
confidence: 99%